Estimation of Arsenic Intake from Drinking Water and Food (Raw and Cooked) in a Rural Village of Northern Chile. Urine as a Biomarker of Recent Exposure - Diaz-Schulze, O; Pastene-Olivares, R; Pastene-Olivares, R (Multidisciplinary Digital Publishing Institute (MDPI), 2015)
The aim of this study was to estimate both the contribution of drinking water and food (raw and cooked) to the total (t-As) and inorganic (i-As) arsenic intake and the exposure of inhabitants of Socaire, a rural village in Chile´s Antofagasta Region, by using urine as biomarker. The i-As intake from food and water was estimated using samples collected between November 2008 and September 2009. A 24-hour dietary recall questionnaire was given to 20 participants. Drinking water, food (raw and cooked) and urine samples were collected directly from the homes where the interviewees lived. The percentage of i-As/t-As in the drinking water that contributed to the total intake was variable (26.8–92.9). Cereals and vegetables are the food groups that contain higher concentrations of i-As. All of the participants interviewed exceeded the reference intake FAO/OMS (149.8 μg·i-As·day−1) by approximately nine times. The concentration of t-As in urine in each individual ranged from 78 to 459 ng·mL−1. Estimated As intake from drinking water and food was not associated with total urinary As concentration. The results show that both drinking water and food substantially contribute to i-As intake and an increased exposure risk to adult residents in contaminated areas. © 2015 by the authors; licensee MDPI, Basel, Switzerland.
Keywords: arsenic; endemic; area; drinking water; food; urine